Emerging markets : lessons for business success and the outlook for different markets - Pacek, Nenad; Thorniley, Daniel, 1955- (London : Profile Books in association with the Economist, 2007)
This book looks at the reasons why some firms fail and others succeed. Full of real-life corporate experience, it analyses the strategic lessons for both those planning to enter and those already operating in emerging markets. It outlines the practical lessons of how, say, you make an acquisition work or deal with issues like corruption. It shows how important it is for those responsible for emerging-market operations to manage the expectations of head office and how important it is for those at head office to make the effort to understand the problems their regional managers face.
Previous ed.: 2004.
Includes index.
nmn 3/06/13
Loans
Keywords: International business enterprises -- Management; International business enterprises -- Developing countries; Developing countries -- Foreign economic relations; Developing countries -- Economic conditions